A First Look at Chorioamnionitis Management Practice Variation among US Obstetricians. (23rd December 2012) - Greenberg, Mara B.; Anderson, Britta L.; Schulkin, Jay; Norton, Mary E.; Aziz, Natali
Abstract : Objective . To examine practice patterns for diagnosis and treatment of chorioamnionitis among US obstetricians. Study Design . We distributed a mail-based survey to members of the American College of Obstetricians and Gynecologists, querying demographics, practice setting, and chorioamnionitis management strategies. We performed univariable and multivariable analyses. Results . Of 500 surveys distributed, 53.8% were returned, and 212 met study criteria and were analyzed. Most respondents work in group practice (66.0%), perform >100 deliveries per year (60.0%), have been in practice >10 years (77.3%), and work in a nonuniversity setting (85.1%). Temperature plus one additional criterion (61.3%) was the most common diagnostic strategy. Over 25 different primary antibiotic regimens were reported, including use of a single agent by 30.0% of respondents. A wide range of postpartum antibiotic duration was reported from no postpartum treatment (34.5% after vaginal delivery, 11.3% after cesarean delivery) to 48 hours of postpartum treatment (24.7% after vaginal delivery, 32.1% after cesarean delivery). No practitioner characteristic was independently associated with diagnostic or therapeutic strategies in multivariable analysis. Conclusion . There is a wide variation in contemporary clinical practices for the management of chorioamnionitis. This may represent a dearth of level I evidence. Future prospective clinical trials may provide more evidence-based practice recommendations for diagnosis and treatment of chorioamnionitis.